PAUL KALANITHI’S PSYCHE AS SEEN IN PAUL KALANITHI’S WHEN BREATH BECOMES AIR - Yuliastuti, Anicleta; Imroatussolihah, Nisfi Juli (Dinamika : Jurnal Sastra dan Budaya, 2017)
The main goal of this research is to find out the psyche of the main character from When Breath Becomes Air novel using qualitative method. Psychoanalysis theory of Sigmund Freud (1856- 1939) is used to analyze the main character by the words and conversation in the novel. The result of this research shows that the psyche of the main character is balance. Id, Ego, and Superego are well played in Paul Kalanithi. In the first time, he is conquered by the Id and the ego tries to fulfill the id?s demand, shows from his passion in writing and studying Literature. By the following time, the superego appears and works as good as its moral principle, describes from his decision for being a doctor to help someone?s life. Furthermore, to make more understand about Paul Kalanithi?s psyche, the causal factors and the effects of his psyche are also analyzed in this research.Key Words: Novel, Character, Psychology, Psychoanalysis, id ego and superego